Grundtvig i finländskt perspektiv - Björkstrand, Gustav (Grundtvig-Studier, 1999)
Grundtvig in a Finnish Perspective By Gustav Björkstrand For several reasons it must cause surprise that Grundtvig did not show more attention to Finland. In Grundtvig’s well-known and noteworthy statements about the Nordic tradition, in which he also referred to the Scandinavian universities, one looks in vain for references to the Finnish institutes of higher education. This fact becomes so much more remarkable when it is considered that in 1835 Grundtvig was invited to become a corresponding member of the Finnish Literary Society. As far as it has been possible to establish, Grundtvig did not reply to the invitation, possibly because of an uncertain knowledge of the Finnish language, even though Grundtvig must have been familiar with the fact that the Swedish language occupied a prominent position in Finland. Likewise, it seems difficult to explain that Grundtvig did not take any great interest in the mythology of old Finland, as it is known for example from the Kalevala legend. It is common knowledge that in Grundtvig’s own lifetime, mid- 19th century Scandinavism included Finland, so that it seems indisputable that this should have reminded Grundtvig of Finland as belonging to the Nordic community. From 1868 the folk high school ideals became known in Finland. Several Finnish writers and educators voiced their enthusiasm about the Danish folk high schools and expressed the wish that the ideas should be realized in Finland, too. There was some discussion, however, whether the inclusion of old Nordic mythology was to rest on an all-Scandinavian basis, or the main stress should be laid on the specifically Finnish mythology. It is possible that uncertainty on this point may have been a contributory cause why no evidence of any interest in Finland can be found even in Grundtvig’s later years. This assumption may find support in yet another aspect of the early debate about the folk high school ideals in Finland; several of the earliest Finnish advocates of the folk high school expressed a strong wish that Bible and Church teaching should have a prominent place, a view that Grundtvig must certainly have disagreed with. From the late 1880s the folk high school in Finland saw a real breakthrough. From the available correspondence between Finnish and Danish folk high school pioneers it may be established that the Finns sought inspiration at the well-known Danish high schools, primarily Askov, but also Valle-kilde, in order to find support there for their endeavours to make the aims behind the folk high school take root in Finland. The most important representative of the early movement in Finland, Sofia Hagman, had been in Denmark as early as 1884. In a book from 1891 about the folk high school in Denmark she was criticized for giving too much attention to the Danish perspectives at the expense of the situation in the other Nordic countries. In any case, there is abundant evidence of the decisive importance that the folk high school ideas acquired in Finland towards the end of the 19th and in the beginning of the 20th centuries. Thus, in 1917, when Finland achieved political indepen-dence, there were 42 folk high schools, 28 of which were Finnish-speaking, while 14 were Swedish-speaking. Through the whole of the 20th century the folk high schools have continued to play an important role, even though aims and practice have been extensively adjusted. It is particularly striking that the schools are increasingly attended by young people wanting to obtain specific qualifications with a view to further education, whereas more universal ideals such as enlightenment for life and the living dialogue seem to have receded into the background. As far as Grundtvig’s hymns are concerned, they have found their way into Finland to some ex-tent, mainly, however, through Swedish-language versions. The best known Grundtvig hymn in both language traditions is Kirken den er et gammelt hus (Our Church it is an Ancient House). In conclusion, the article deals with the research carried out in Finland on Grundtvig and the hi-story of his influence (Wirkungsgeschichte). The historical background is that nowhere else has the folk high school had such effect and such impact. The writer of the present article (Gustav Björkstrand) has contributed himself with a monograph from 1981 about the folk high school in the Swedish-speaking part of Finland, viewed in relation to the mobilization of the common people. The main conclusion is that the importance of the folk high school has primarily depended on three factors: the endeavour to awaken the common people to the defence against Russification, the struggle to arouse an interest in Swedish language and culture, and finally the fight against secularization in defence of Christian values.